2017
DOI: 10.1038/s41598-017-13220-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean warming on sustainable fisheries management informs the Ecosystem Approach to Fisheries

Abstract: An integrated ecosystem model including fishing and the impact of rising temperatures, relative to species’ thermal ranges, was used to assess the cumulative effect of future climate change and sustainable levels of fishing pressure on selected target species. Historically, important stocks of cod and whiting showed declining trends caused by high fisheries exploitation and strong top-down control by their main predators (grey seals and saithe). In a no-change climate scenario these stocks recovered under sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 77 publications
0
65
0
Order By: Relevance
“…For instance, Hidalgo et al (2011) showed that the erosion of the age structure of harvested hake populations in the Mediterranean Sea may drastically alter their capacity to dampen environmental fluctuations. Ignoring the effects of climate change in stock assessment could compromise the validity of stock forecasts and affect the robustness of several biological reference points such as the Maximum Sustainable Yield (MSY) (Brander, 2010;Grafton, 2010;Link et al, 2011;Galbraith et al, 2017;Serpetti et al, 2017). However, improved fisheries and ecosystems management in a highly overexploited Mediterranean Sea could have the potential to offset many negative effects of climate change (Roberts et al, 2017;Gaines et al, 2018).…”
Section: Structure and Functioning Of The Mediterranean Sea Ecosystemmentioning
confidence: 99%
“…For instance, Hidalgo et al (2011) showed that the erosion of the age structure of harvested hake populations in the Mediterranean Sea may drastically alter their capacity to dampen environmental fluctuations. Ignoring the effects of climate change in stock assessment could compromise the validity of stock forecasts and affect the robustness of several biological reference points such as the Maximum Sustainable Yield (MSY) (Brander, 2010;Grafton, 2010;Link et al, 2011;Galbraith et al, 2017;Serpetti et al, 2017). However, improved fisheries and ecosystems management in a highly overexploited Mediterranean Sea could have the potential to offset many negative effects of climate change (Roberts et al, 2017;Gaines et al, 2018).…”
Section: Structure and Functioning Of The Mediterranean Sea Ecosystemmentioning
confidence: 99%
“…Food-web models can represent a useful tool for MPA assessment that can help to identify ecological trade-offs and synergies [72]. Results also show that trade-offs must be considered between fisheries management and climate change [73] and emphasize the need to include other stressors than fisheries to appropriately assess the future of marine ecosystems [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Dive effort, including time spent diving, is also adjusted to increase energetic gain of foraging bouts in gray seals (Austin et al 2006). Thus changes in marine mammal diving behavior reflect environmental changes and shifts in ecosystem resources, which have not only ecological implications but can also be important from the perspective of human fisheries (Serpetti et al 2017). Additionally, the results of this study demonstrate the potential for undesirable activity or in-activity of immune cells to result from such changes in dive behavior caused by either foraging needs or stressors such as human disturbance or anthropogenic noise.…”
Section: Discussionmentioning
confidence: 99%